Evaluation of the bead enzyme-linked immunosorbent assay for detection of cholera toxin directly from stool specimens. - Ramamurthy, T (1992)
A highly sensitive bead enzyme-linked immunosorbent assay (bead ELISA) for detection of cholera toxin (CT) was evaluated for direct detection of CT from stool specimens of patients with acute secretory diarrhea. Of the 75 stool samples examined, 59 yielded biochemically, and serologically confirmed strains of Vibrio cholerae O1. The bead ELISA was positive for CT in stool supernatants in 50 (84.7%) of the 59 samples from which V. cholerae O1 was isolated. In addition, the bead ELISA was positive for three stool specimens which were negative by culture. The free CT present in 48 of the 50 stool samples positive by culture for V. cholerae O1 and for CT by bead ELISA was completely absorbed by anti-CT immunoglobulin G. All of the 59 strains of V. cholerae O1 biotype eltor isolated in this study produced in vitro CT. The concentration of CT present in the bead ELISA-positive stool samples ranged between 26 pg/ml and greater than 100 ng/ml. This evaluation study demonstrates that the bead ELISA is a sensitive and simple method for direct detection of CT in nonsterile stool samples, and we recommend routine use of this assay for detection of CT in stool samples and culture supernatants in clinical and reference laboratories.